Respuesta :
For this case we must simplify the following expression:
[tex]1,075 (5.25) x-5.25 (0.25) (x-3) =[/tex]
So, solving the first parentheses we have:
[tex]5.64375x-1.3125 (x-3) =[/tex]
We have to:
[tex]- * + = -\\- * - = +\\5.64375x-1.3125x + 1.3125 (3) =\\5.64375x-1.3125x + 3.9375 =[/tex]
We add similar terms taking into account that different signs are subtracted and the sign of the major is placed:
[tex]4.33125x + 3.9375[/tex]
Finally, the simplified expression is: [tex]4.33125x + 3.9375[/tex]
ANswer:
[tex]4.33125x + 3.9375[/tex]